Chemical looping gasification of biochar to produce hydrogen-rich syngas using Fe/Ca-based oxygen carrier prepared by coprecipitation. (February 2021) - Hu, Zhifeng; Miao, Zhenwu; Chen, Haonan; Wu, Jiawei; Wu, Wencheng; Ren, Yongzhi; Jiang, Enchen
Abstract: Biochar chemical looping gasification (CLG) is a novel technology to obtain hydrogen-rich syngas, high gasification efficiency and low carbon deposition. This study investigates the effect of preparation methods, Fe loadings, active components, Ca loadings and steam/biochar (S/C) to achieve the optimal oxygen carrier. The results show that coprecipitation is the best preparation method to gain highest efficiency, redox activity and dispersion. H2 production increases visibly with the increase of Fe loading, while efficiencies increase firstly and then decrease. There is an evident effect of active component on CLG. Oxygen carrier based on Fe/Ca performs a lower carbon deposition, higher H2 production and efficiency. With the increase of Ca loading, H2 production and efficiencies increase firstly and then decrease. S/C has an obvious effect on CLG performance. 1.5 is the optimal S/C to achieve high H2 concentration of 67.35%, the highest gas production of 1.34 Nm 3 /kg and gasification efficiency of 96.93%. Graphical abstract: Image 1 Highlights: Fe/Ca-based oxygen carrier performs synergistic catalysis in biochar CLG process. Coprecipitation method is conducive to dispersion, redox reaction and efficiency. The optimal Fe loading is 1.5 with the highest efficiency and interaction of carrier. 1.0 is the best Ca loading to gain highest efficiencies and lowest carbon deposition. Steam/biochar has an obvious effect on H2 production and efficiencies.